A Study of the Effect of the North Atlantic Oscillations with Temperature and Precipitation in Baghdad City - Alobaidi, Abdulwahab H.; Taresh, Oroba J.; Mjeed, Hussam T. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The aim of this research is to study the effects of the North Atlantic Oscillation (NAO) on the temperature and precipitation patterns in Baghdad city. Data of the monthly means of the NAO index,the monthlymeans of temperature, and the monthly total of precipitation were analyzed for the period 1900-2008. Non-parametric tests were used to investigate the correlations between these variables. The time series of temperature and precipitation showed no trends. The results indicated that is a slight correlation between the NAO and temperature and precipitation suggesting that NAO has no major effects on the temperature and precipitation patterns in Baghdad city.